Evaluasi Kepuasan Pengguna Pada Website CDC Unsri Menggunakan Metode End User Computing Satisfaction (EUCS) - Adelia Faradilla; Dwi Rosa Indah; Putri Eka Sevtiyuni (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Sriwijaya University Career Development Center has applied information technology through a website that serves to provide information and services regarding character and career development of students and alumni. Based on interviews with several users, it is suspected that there are problems on the website, such as information that is not up to date, the user interface is considered less attractive and makes users feel difficulties and problems in website access speed. For this reason, it is necessary to evaluate user satisfaction to determine the level of user satisfaction on the Unsri CDC website so that it can be used as reference material in improving website quality in the future. In evaluating user satisfaction using the End User Computing Satisfaction (EUCS) method which consists of 5 variables in it including Content, Accuracy, Format, Ease of Use and Timeliness. This study included 150 respondents consisting of students and alumni of Sriwijaya University who had accessed the Unsri CDC website. The results showed that the level of user satisfaction in each variable, namely Content worth 82.6%, Accuracy worth 77.3%, Format worth 76.8%, Ease of Use worth 77.7% and Timeliness worth 76.1%.